Synthesis methods of 1,2,4-triazole-3-thiones: review - Frolova, Yu. S.; Kaplaushenko, A. H.; Ihnatova, T. V.; Kaplaushenko, T. M.; Фролова, Юлія Сергіївна; Каплаушенко, Андрій Григорович; Ігнатова, Т. В.; Каплаушенко, Т. М. (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the study was to analyze in detail and combine the available literature materials to study the reactions associated with the formation of different classes of derivatives of 1,2,4-triazole-3-thione and to study their physical-chemical properties. Various innovative methods have been proposed and explored for synthesizing different classes of 1,2,4-triazole compounds, each with distinct applications and potential medicinal benefits. When analyzing the outcomes of studies aimed at obtaining new 1,2,4-triazole-3- thiones, it’s crucial to recognize the multiple stages involved in their synthesis. These stages typically include the esterification of carboxylic acids, hydrazinolysis, the formation of carbothioamides, and thiones through alkaline cyclization. Subsequently, reactions involving the S-function are conducted, leading to the formation of various classes of derivatives of 1,2,4-triazole. The study by a team of scientists introduced a novel method for synthesizing imidazolyl- and imidazole-1,2,4-triazoles, targeting the design of safer analgesic and anti-inflammatory agents. Moreover, researchers have successfully synthesized derivatives of 3-[2-(5-thio-4-aryl-4H-1,2,4-triazole-3-yl)ethyl]quinoxalin-2(1H)-one, N-(3-thio-5-aryl-[1,2,4]triazole-4-yl)acylamides, 5-alkylthio-4-amino-3-(5,7-dimethyl-1,2,4-triazolo[1,5-a]pyrimidine-2-thiomethyl)-1,2,4-triazole and 3-(5,7-dimethyl-1,2,4-triazolo[1,5-a]pyrimidine-2-thiomethyl)-6-aryl-5,6-dihydrogen-1,2,4-triazole-[3,4-b]-1,3,4-thiadiazole, 5,5’-(alkyldiyl-bis(sulfandiyl))bis(N-(arylidene)-3-thiophen-2-ylmethyl)-4H-1,2,4-triazole-4-amines, 3-(arylsulfonyl)-4-phenyl-5-(3,4,5-trimethoxyphenyl)- 4H-1,2,4-triazole, expanding the scope of 1,2,4-triazole-based, compounds with potential pharmacological activities. Furthermore, the synthesis of molecules containing two 1,2,4-triazole and two benzole rings has gained traction, offering new avenues for drug development. Мета роботи – детально проаналізувати й об’єднати відомості наукової літератури щодо вивчення реакцій, пов’язаних з утворенням різних класів похідних 1,2,4-тріазол-3-тіону, а також вивчити їхні фізико-хімічні властивості. Запропоновано та досліджено інноваційні методи синтезу різних класів сполук 1,2,4-тріазолу; кожен із них застосовують, і кожен має потенційну медичну користь.Під час аналізу результатів досліджень, спрямованих на отримання нових 1,2,4-тріазол-3-тіонів, важливо розрізняти етапи їх синтезу. Ці стадії зазвичай включають етерифікацію карбонових кислот, гідразиноліз, утворення карботіоамідів і тіонів шляхом лужної циклізації. Згодом проводять реакції за участю S-функції, що призводять до утворення різних класів похідних 1,2,4-тріазолу. Розроблено новий метод синтезу імідазоліл- та імідазол-1,2,4-тріазолів, спрямований на розробку безпечніших анальгетиків і протизапальних засобів. Синтезовано похідні 3-[2-(5-тіо-4-арил-4Н-1,2,4-тріазол-3-іл)етил]хіноксалін-2(1Н)-ону, N-(3-тіо-5-арил-[1,2,4]тріазол-4-іл)ациламіди, 5-алкілтіо-4-аміно-3-(5,7-диметил-1,2,4-тріазоло[1,5-а]піримідин-2-тіометил)-1,2,4-тріазол і 3-(5,7-диметил-1,2,4-тріазоло[1,5-а] піримідин-2-тіометил)-6-арил-5,6-дигідроген-1,2,4-тріазол-[3,4-b]-1,3,4-тіадіазол, 5,5’-(алкілдііл-біс(сульфандііл))біс(N-(ариліден)-3-тіофен-2-ілметил)-4Н-1,2,4-тріазол-4-аміни, 3-(арилсульфоніл)-4-феніл-5-(3,4,5-триметоксифеніл)-4Н-1,2,4-тріазол, що розширює сферу застосування сполук на основі 1,2,4-тріазолу з потенційною фармакологічною активністю. Перспективним для розроблення ліків є синтез молекул, що містять два 1,2,4-тріазолових і два бензольних кільця.
Методи синтезу 1,2,4-тріазол-3-тіонів: огляд
Frolova Yu. S. - ORCID ID: 0000-0002-3995-5088; Kaplaushenko A. H. - ORCID ID: 0000-0003-3704-5539; Kaplaushenko T. M. - ORCID ID: 0000-0001-5092-3370.
Keywords: 1,2,4-triazole; physical-chemical properties; transformation; 1,2,4-тріазол; фізико-хімічні властивості; перетворення